Alternative irrigation : the promise of runoff agriculture - Barrow, Christopher J. (London : Earthscan, 1999)
"Runoff agriculture uses surface and subsurface water which is often otherwise overlooked and wasted. It enables small farmers as well as commercial agriculturalists to improve yields and security of harvest, even in harsh and remote environments." "The author introduces the techniques and strategies, as well as the challenges and the potential of this crucial approach, which can contribute so much to reducing land degradation and improving conservation and sustainability." "This book is an essential tool for teaching and research, as well as for practical application by agricultural and development organizations and workers."--Jacket.
1. Introduction -- 2. Soil and Water Conservation (SWC) -- 3. Runoff Harvesting and Storage -- 4. Ephemeral and Variable Streamflow: Spate, Wetlands and Flood Agriculture -- 5. Indigenous Runoff Agriculture: Challenges and Breakdown -- 6. Expanding, Upgrading and Rehabilitating Runoff Agriculture -- 7. The Future for Runoff Agriculture.
Includes bibliographical references (pages 140-165) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Runoff irrigation; Irrigation par ruissellement; TECHNOLOGY & ENGINEERING -- Agriculture -- Irrigation; Runoff irrigation